2021
DOI: 10.1108/et-06-2020-0179
|View full text |Cite
|
Sign up to set email alerts
|

Institutional factors for faculty members' implementation of blended learning in higher education

Abstract: PurposeThe aim of this study is to develop a model grounded by the institutional theory to investigate blended learning (BL) implementation among faculty members in higher education and further validate the model.Design/methodology/approachQuantitative methodology was employed, and data were gathered through questionnaires among 188 e-learning directors, managers and coordinators at faculty/department in institutions, which implement BL.FindingsFindings reveal that BL implementation by faculty members is signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Designing a BL model becomes an instructional innovation during the pandemic. Instructional innovations must be able to increase result learning [6], [10] with mixed classroom (onsite) and e-learning (online) [11]. The BL model provides broad opportunities for students to learn [4], [12].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Designing a BL model becomes an instructional innovation during the pandemic. Instructional innovations must be able to increase result learning [6], [10] with mixed classroom (onsite) and e-learning (online) [11]. The BL model provides broad opportunities for students to learn [4], [12].…”
Section: Resultsmentioning
confidence: 99%
“…Ustun et al [38] reported a study to assist and teach a BL course in higher education. Bokolo Anthony [6] reported faculty institutional initiatives that affect the implementation of BL. Mülle et al [39] reviewed the impact of replacing classroom time with BL on higher education institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Blended learning in higher education Within higher education, blended learning has received much scholarly attention over recent years (Anthony, 2021b;Anthony et al, 2020;Dziuban et al, 2018). As a complete examination of blended learning in higher education would be beyond the scope of this article, this section provides a brief overview of recently published review articles on the subject.…”
mentioning
confidence: 99%